Islam dan Panorama Keagamaan Masyarakat Tatar Sunda - Undang Ahmad Darsa (JURNAL INDO-ISLAMIKA, 2017)
This article uses the terms “Tatar Sunda” to refer geographically to a region that stretches from the Sunda Strait (Selat Sunda/Ujung Kulon) to some of the Central Javanese territorries bordering with Cipamali/Kalipamali in Brebes in the Central Java and Kali Serayu in South of Central Java next to Cilacap. This paper argues that the religious life in the Sundanese Tatar historically and culturally took place peacefully. This paper bases this argument on the Sundanese manuscripts saying that the Hinduization process in the Tatar Sunda was mostly derived from the Hindu kingdoms’ elites in the Tatar Sunda. In contrast, the process of Islamization in the Tatar Sunda was instigated from the lower classes (ordinary people). Meanwhile, some of these elites and some of the Sundanese people were able to welcome and accept Islam. Moreover, some of these Hindu elites were voluntarily converted to Islam.